An Experimental Assessment on the Influence of Carbon Nanotubes Matrix Charging on the Fatigue Behavior of Composite Laminates. Issue 1 (21st August 2022) - Russo, Angela; Meo, Michele; Zarrelli, Mauro; Flora, Francesco; Riccio, Aniello
Abstract: In this work, an experimental preliminary assessment on the fatigue behavior of nanomodified composite coupons has been attempted. Comparisons between the fatigue life of epoxy resin/carbon fiber neat coupons and epoxy resin/carbon fiber specimens reinforced with nanoparticles have been carried out. Tensile, compressive, and in‐plane shear samples have been manufactured according to ASTM D3039, ASTM D3410, and ASTM D3518 standards, respectively. The coupons, both with neat and nanomodified epoxy resin, have been tested under tension‐tension, compression‐compression and in‐plane shear fatigue loading conditions to understand the effect of the nanoparticles' addition on the fatigue behavior of thermosetting epoxy resin.